2021
DOI: 10.1038/s41416-021-01663-9
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of molecular tumour board discussion on targeted therapy allocation in advanced prostate cancer

Abstract: Background Molecular tumour boards (MTB) optimally match oncological therapies to patients with genetic aberrations. Prostate cancer (PCa) is underrepresented in these MTB discussions. This study describes the impact of routine genetic profiling and MTB referral on the outcome of PCa patients in a tertiary referral centre. Methods All PCa patients that received next-generation sequencing results and/or were discussed at an MTB between Jan 1, 2017 and Jan 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…When patient allocation into precision medicine trials is necessary, there was fair agreement (74%) that tumour genetic testing should ideally be performed in treatment-naïve mCRPC ( Supplementary material ). According to a recent study, 45.5% of Dutch patients harbour one or more actionable alterations in genes as per the ESMO Precision Medicine Working Group recommendation, with >60% of patients allocated within a precision medicine trial, including the Drug Rediscovery Protocol (DRUP) trial running in over 30 Dutch centres [33] . As targeted therapy and immunotherapy within this trial can be administered only after NHAs and taxanes, some panellists believed that many patients would not be suitable study candidates when tested in end-stage (mCRPC) disease.…”
Section: Discussionmentioning
confidence: 99%
“…When patient allocation into precision medicine trials is necessary, there was fair agreement (74%) that tumour genetic testing should ideally be performed in treatment-naïve mCRPC ( Supplementary material ). According to a recent study, 45.5% of Dutch patients harbour one or more actionable alterations in genes as per the ESMO Precision Medicine Working Group recommendation, with >60% of patients allocated within a precision medicine trial, including the Drug Rediscovery Protocol (DRUP) trial running in over 30 Dutch centres [33] . As targeted therapy and immunotherapy within this trial can be administered only after NHAs and taxanes, some panellists believed that many patients would not be suitable study candidates when tested in end-stage (mCRPC) disease.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the impact of MTB on the implementation processes for personalised cancer medicine [95]. MTBs were shown to improve the accuracy of genomic data interpretation and increased the proportion of patients who received targeted therapy [96][97][98]. This also includes improvement of the capacity to communicate with patients by facilitating the presentation of genomic information [99].…”
Section: Molecular Tumour Boardsmentioning
confidence: 99%
“…Several studies have demonstrated the impact of MTB on the implementation processes for personalized cancer medicine [ 123 ]. MTBs have been shown to improve the accuracy of genomic data interpretation and increase the proportion of patients who received targeted therapy [ 130 , 131 , 132 ]. This also includes the improvement of the capacity to communicate with patients by facilitating the presentation of genomic information [ 133 ].…”
Section: New Forms Of Organization That Bridge the Dividementioning
confidence: 99%